Empowering the Great Energy Transition : Policy for a Low-Carbon Future - Valentine, Scott; Brown, Marilyn; Sovacool, Benjamin (Columbia University Press, 2019)
At a time when climate-change deniers hold the reins of power in the United States, what options are available to cities, companies, and consumers around the world who seek a cleaner future? In this book, Scott Victor Valentine, Marilyn A. Brown, and Benjamin K. Sovacool explore the many developments that give reason for optimism. They provide an expert analysis of the achievable steps that citizens, organizational leaders, and policy makers can take to put their commitments to sustainability into practice.Empowering the Great Energy Transition demonstrates that a transition away from carbon-intensive energy sources is inevitable-if we can overcome the forces supporting incumbent technologies. Valentine, Brown, and Sovacool offer ways to expedite the transition, showing that low-carbon renewable-energy technologies have advanced and solutions for improving energy efficiency are becoming cost-competitive. However, new policies and business models are needed to surmount the hurdles between the current consumption model and cleaner energy. The book emphasizes the need to center energy around climate justice, with special consideration of the effects on public resources and vulnerable groups. Empowering the Great Energy Transition shows that with just a few adjustments, we can set humanity on a course that supports entrepreneurs and communities in mitigating the environmental harm caused by technologies whose time has come and gone.